Efficacy of a Blended Learning Mastery Progression Cycle on Student Achievement and Attitude in High School Science - Roberson, Sam Peter (Curtin University, 2020)
This study was conducted to examine the effect of a Blended Learning Mastery Progression Cycle on student achievement and attitude in a High School Physics context.It was concluded that the use of the Blended Learning Mastery Progression Cycle led to improvements in understanding. These findings indicate that the use of Blended Learning activities as correctives is an effective way of improving students’ understanding of the Newtonian Force Concept.